Study on the foam production characteristics of air self-suction foam generator by jet - Caiyuan Lu; Yuxin Wu; Di Zhu; Yuntao Liang (Scientific Reports)
Abstract Confined space fires could easily cause serious casualties and property damage, and foam is an effective means of preventing confined space fires. The existing foam generator does not have both momentum and foam expansion rate (FER) and is poorly suited to confined spaces. In order to develop a foam generator suitable for confined space fire protection, an in-depth analysis of the physical foaming characteristics of self-suction foam is required, and the structure of the foam generator is optimized accordingly. For this reason, this paper analyzes the foaming characteristics and forming principle of air self-suction foam generator, and simulates and studies the over-current ratio of rectifying orifice plate with the help of Fluent software, $$φ$$ (the ratio of the area of the fluid that can pass through the rectifier disk to the vertical cross-sectional area of the fluid flow), the distribution patterns of flow field, pressure, and turbulence intensity inside the foaming machine are determined by the nozzle cavity spacing and mixing cavity diameter. The study demonstrates that water flow is the most effective means of entraining air, and that the contact between the fluid and foam network is most thorough when the overflow ratio of the fan disc ( $$φ$$ ) is 0.455, the distance between nozzle cavities $$μ$$ (the distance between the nozzle and the closest end face of the foam chamber vertically.) is 200 mm, and the diameter of the mixing chamber ( $${d}$$ ) is 260 mm. These conditions are optimal for the foam generator. Experimental verification shows that the device has the strongest air entrainment capability at $$φ$$ 0.455. The foam mesh number ( $${m}$$ ), foam mesh spacing ( $${\ell}$$ ), and number of layers of foam mesh ( $${n}$$ ) significantly impact the air self-solution foaming of the jet. These factors influence FER, range (L), foam stacking thickness ( $$σ$$ ), and unfoamed liquid separation rate (γ, Foam solution not involved in the foaming process.), but the magnitude of their effect varies. Considering the four factors affecting foam production performance, the optimal effect is achieved when the foam mesh of 16, the foam mesh spacing of 3 cm, the foam mesh of 2 layers, the distance between the foam mesh and the nozzle is 22 cm and $$φ$$ is 0.455. Under these conditions, the foaming ratio (FER) of the jet self-suction foaming machine is 42 times, with L at 13 m, σ at 7 cm, and γ at 0.15 L/s. A device has been developed for long-distance and high FER air self-suction of foam generator, which can significantly assist in fire prevention and extinguishing in confined spaces.